Employment Outcomes of Office Administration Graduates of Bohol Island State University - Candijay Campus, Philippines - Zapanta, Ashley; Lebita, Jennilyn; De la Peña, Vicenta; Suso, Jaycel; Casundo, Deliarita; Cano, Jesszon (Journal of Interdisciplinary Perspectives, 2025)
This tracer study aimed to assess the employability of Bachelor of Science in Office Administration graduates from Bohol Island State University - Candijay Campus (2021–2023) and evaluate how their competencies align with workforce demands. Employability is a key indicator of a university's success in preparing graduates for professional careers, directly influencing institutional reputation and graduate career outcomes. Using a modified Graduate Tracer Study (GTS) questionnaire, quantitative data were collected through online surveys targeting 245 graduates, yielding 143 responses. Statistical analysis revealed that most respondents were female, single, and employed as office or clerical staff. Many earned monthly salaries ranging from PHP 10,000 to PHP 20,000, with salary and benefits highlighted as critical factors in job satisfaction. Lack of work experience was identified as the primary barrier to employment, underscoring its importance in hiring. Furthermore, the alignment between graduates' fields of study and their current roles demonstrated the relevance of the program's curriculum to industry needs. Graduates identified communication skills as the most valuable competency acquired during their studies, reflecting the effectiveness of the university's curricular offerings in equipping students for professional success. This study contributes to understanding graduate employability by emphasizing the role of targeted skill development and work experience in enhancing career readiness.